Immunophenotype and Immune-Modulatory Activities of Human Fetal Cartilage-Derived Progenitor Cells. Issue 7 (July 2019) - Lee, Su Jeong; Kim, Jiyoung; Choi, Woo Hee; Park, So Ra; Choi, Byung Hyune; Min, Byoung-Hyun
We have previously reported human fetal cartilage progenitor cells (hFCPCs) as a novel source of therapeutic cells showing high proliferation and stem cell properties superior to those of adult mesenchymal stem cells (MSCs). In this study, we investigated the immunophenotype and immune-modulatory activities of hFCPCs. With institutional review board approval, hFCPCs were isolated from fetuses at 11–13 weeks of gestation. hFCPCs showed strong expression of HLA class I molecules but low or no expression of HLA class II and co-stimulatory molecules, which was not changed significantly after 4 days of IFN-γ treatment. In a mixed lymphocyte reaction (MLR), hFCPCs showed no allogeneic immune response to peripheral blood lymphocytes (PBLs) and suppressed concanavalin A (Con A)-mediated proliferation of PBLs in a dose-dependent manner. In addition, hFCPCs inhibited Con A-induced secretion of pro-inflammatory cytokines TNF-α and IFN-γ from PBLs but showed no significant decrease of secretion of IL-10, anti-inflammatory cytokine. Co-culture of hFCPCs with stimulated PBLs for 4 days resulted in a significant increase in CD4 + CD25 + FoxP3 + T regulatory cells (Tregs). hFCPCs expressed LIF, TGF-β1, TSG-6, and sHLA-G5 but did not express IDO and HGF. Stimulation of hFCPCs with TNF-α for 12 h showed slight induction in the expression of LIF, TSG-6, IDO, and HGF, whereas stimulation with IFN-γ did not affect expression of any of these factors. These results suggest that hFCPCs have low allogeneic immunogenicity and immune-modulatory activity in vitro, comparable to those of MSCs. However, compared with MSCs, hFCPCs were less responsive to TNF-α and IFN-γ, and the mechanisms underlying responses to these two cell types appeared distinct.